2016
DOI: 10.1017/s0024282916000086
|View full text |Cite
|
Sign up to set email alerts
|

Increased snow accumulation reduces survival and growth in dominant mat-forming arctic-alpine lichens

Abstract: Relative growth rates (RGR) and carbon-based secondary compounds (CBSCs) were quantified in four dominant terricolous arctic-alpine mat-forming lichens with different preferences for snow cover. The aim was to evaluate the effects of snow depth, and thus snow cover duration, on lichen growth and performance. The species,Alectoria ochroleuca,Flavocetraria nivalis,Cladonia mitisandCetrariella delisei, are associated with increasing snow depth, respectively. They were transplanted for one year at five snow depths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Because intraspecific variability can help maintain community stability and functioning under changing environmental conditions (Jung, Violle, Mondy, Hoffmann, & Muller, ; Malyshev et al, ), the lichen communities would be more likely to resist environmental change than the bryophyte and vascular plant communities which lack the intraspecific plasticity needed to cope with environmental change. This line of thought is contrasted by studies showing that lichen (and bryophyte) communities respond negatively in terms of diversity and abundance to global change phenomena such as increased temperatures and changes in precipitation and snow cover (Alatalo, Jägerbrand, Chen, & Molau, ; Bidussi et al, ; Elmendorf et al, ; Jägerbrand, Kudo, Alatalo, & Molau, ; Lang et al, ). In most of these studies, the decline of non‐vascular vegetation observed under climate warming is likely due to increased competition from vascular plants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because intraspecific variability can help maintain community stability and functioning under changing environmental conditions (Jung, Violle, Mondy, Hoffmann, & Muller, ; Malyshev et al, ), the lichen communities would be more likely to resist environmental change than the bryophyte and vascular plant communities which lack the intraspecific plasticity needed to cope with environmental change. This line of thought is contrasted by studies showing that lichen (and bryophyte) communities respond negatively in terms of diversity and abundance to global change phenomena such as increased temperatures and changes in precipitation and snow cover (Alatalo, Jägerbrand, Chen, & Molau, ; Bidussi et al, ; Elmendorf et al, ; Jägerbrand, Kudo, Alatalo, & Molau, ; Lang et al, ). In most of these studies, the decline of non‐vascular vegetation observed under climate warming is likely due to increased competition from vascular plants.…”
Section: Discussionmentioning
confidence: 98%
“…czerepanovii ). Because many lichens respond negatively to snow cover (Bidussi, Solhaug, & Gauslaa, ; Niittynen & Luoto, ) and are therefore absent from depressions in the landscape where snow accumulates, we selected sites on exposed ridges that support communities with a mixed cover of vascular plants, lichens and bryophytes. The vascular plant communities are relatively species poor, with Empetrum nigrum , Vaccinium uliginosum and Betula nana as most common at the lowest elevations and Carex bigelowii and Salix herbacea at the higher elevations.…”
Section: Methodsmentioning
confidence: 99%
“…It is also known that lichens show differential sensitivity to snow burial 1517 . Snowkill is expected, therefore, to not only lead to the death of some lichens but also to consequential changes in biodiversity because of their different sensitivities.…”
Section: Discussionmentioning
confidence: 99%
“…Some lichen CBSCs degrade fairly quickly during thallus senescence, suggesting that they only impact micro‐arthropods during the early stages of decomposition (Asplund & Wardle, ). However, other compounds are more recalcitrant and thus increase in concentration relative to thallus litter mass, and are therefore likely to have longer term effects on micro‐arthropod feeding activity (Bidussi, Solhaug & Gauslaa, ).…”
Section: How Variation Among Lichens Affects Ecosystem Nutrient and Cmentioning
confidence: 99%